Context-aware mass customization construction system: methods for user captured as-built plans - Brandão, F. J. S.; Paio, A. (Intelligent and informed: proceedings of the 24th International Conference on Computer-Aided Architectural Design Research in Asia, 2019)
The problem of context, a fundamental aspect of dealing with built environments, has not been adequately addressed by mass customization systems so far, which has limited their scope of application. The aim of the present article is to evaluate the adequacy of existing methods of producing as-built plans of rooms by non-expert users for the automatic generation and production of partition walls for building renovation. This paper highlights criteria to develop appropriate methods of capturing context for mass customization construction systems.